Pamrevlumab, an anti-connective tissue growth factor therapy, for idiopathic pulmonary fibrosis (PRAISE): a phase 2, randomised, double-blind, placebo-controlled trial. Issue 1 (January 2020) - Richeldi, Luca; Fernández Pérez, Evans R; Costabel, Ulrich; Albera, Carlo; Lederer, David J; Flaherty, Kevin R; Ettinger, Neil; Perez, Rafael; Scholand, Mary Beth; Goldin, Jonathan; Peony Yu, Kin-Hung; Neff, Thomas; et al.
Summary: Background: Connective tissue growth factor (CTGF) is a secreted glycoprotein that has a central role in the process of fibrosis. This study was designed to assess the safety, tolerability, and efficacy of pamrevlumab (FG-3019), a fully recombinant human monoclonal antibody against CTGF, in idiopathic pulmonary fibrosis. The aim was to establish whether pamrevlumab could slow, stop, or reverse progression of idiopathic pulmonary fibrosis. Methods: The phase 2, randomised, double-blind, placebo-controlled PRAISE trial was done at 39 medical centres in seven countries (Australia, Bulgaria, Canada, India, New Zealand, South Africa, and the USA). Patients with idiopathic pulmonary fibrosis and percentage of predicted forced vital capacity (FVC) of 55% or greater were enrolled and randomly assigned (1:1) by use of interactive responsive technology to intravenous infusion of pamrevlumab 30 mg/kg or placebo every 3 weeks over 48 weeks (16 infusions). The primary efficacy outcome was change from baseline in percentage of predicted FVC at week 48. Disease progression (defined as a decline from baseline in percentage of predicted FVC of ≥10%, or death) at week 48 was a key secondary efficacy outcome. All patients in the pamrevlumab group received at least one dose of the study drug and were analysed for safety. Two patients in the placebo group were excluded from the intention-to-treat population for the efficacy analyses because of enrolment error. This trial is registered with ClinicalTrials.gov, NCT01890265 . Findings: Between Aug 17, 2013, and July 21, 2017, 103 patients were randomly assigned (50 to pamrevlumab and 53 to placebo). Pamrevlumab reduced the decline in percentage of predicted FVC by 60·3% at week 48 (mean change from baseline −2·9% with pamrevlumab vs −7·2% with placebo; between-group difference 4·3% [95% CI 0·4–8·3]; p=0·033). The proportion of patients with disease progression was lower in the pamrevlumab group than in the placebo group at week 48 (10·0% vs 31·4%; p=0·013). Pamrevlumab was well tolerated, with a safety profile similar to that of placebo. Treatment-emergent serious adverse events were observed in 12 (24%) patients in the pamrevlumab group and eight (15%) in the placebo group, with three patients on pamrevlumab and seven on placebo discontinuing treatment. Of the three (6%) deaths in the pamrevlumab group and six (11%) in the placebo group, none was considered treatment related. Interpretation: Pamrevlumab attenuated progression of idiopathic pulmonary fibrosis and was well tolerated. Now in phase 3 development, pamrevlumab shows promise as a novel, safe, and effective treatment for idiopathic pulmonary fibrosis. Funding: FibroGen.